A proposed framework on the affective design of eco-product labels - Gutierrez, Alma Maria Jennifer (Animo Repository, 2020)
There was a shift in sustainability consumption in the last decade that stimulated new strategies for ecological friendly industries and new product innovations. Environmental labeling is a marketing technique used to inform consumers that a company has employed a process to protect the environment. However, uncertainty remains concerning how eco-labels influence consumers. Buying green products can elicit emotion in consumers. When consumers buy eco-products, they feel that they are helping save the environment. Products provide certain emotional benefits and therefore affect mood and behavior. This study aims to examine how consumers who differ in environmental attitudes respond to eco-labels. Aside from this, it wants to determine the intensity and type of emotions elicited by these kinds of products based on a certain set of pre-purchase emotions. These emotions are still unknown. Also, it proposes the Green Emotion Model (GEM) 2.0 that correlates environmental attitudes, visual attention towards these eco-labels, emotion and the desirability of purchasing a product. This framework proposes that the environmental attitudes and awareness of consumers are crucial for them to look for this eco-label on a product. These environmental labels should be able to capture the attention of consumers and thus will provoke positive emotions and lead to the purchase of an eco-product. © 2020 by The Autors.